Chapter 2: Workplace innovation at the digital frontier - Dhondt, Steven (Edward Elgar Publishing, 2023)
The organisational context mediates the relationship between technology and work impact. This reality is not recognised, nor acknowledged, in many studies. However, the European Company Survey 2019 has revealed this relationship in European companies. This mediating role of the organisational context has not yet been sufficiently explored. Thirty company cases performing at the digital frontier were examined for their organisational model, technology, decision context, and handling of work impact. Companies with a workplace innovation model ensure that the impact of digital technology on employees is channelled differently from companies that follow a model of low investment and low involvement. Workplace innovation cases let employees play a stronger role in shaping digital transformation. Cases investing in workplace innovation show more investment in digital technologies.